Contact Pin-Printing onto Porous Silicon for Creating Microarrays with High Chemical Diversity. Issue 10 (October 2016) - Horner, Ian J.; Kraut, Nadine D.; Richardson, Caley A.; Jean, Bernandie; Rook, Alyssa M.; Bright, Frank V.
We explore the size and spatial microheterogeneity of contact pin-printed spots formed on porous silicon (pSi). Glycerol was contact printed at room temperature onto as-prepared, hydrogen-passivated pSi (ap-pSi) using 50 or 200 µm diameter solid pins. The pSi was then subjected to a strong oxidizing environment (gaseous O3 ) and washed to remove the glycerol masks. The glycerol-free regions were converted to oxidized pSi (ox-pSi); the glycerol-coated regions were protected from O3, but not entirely. The final array is described as circularly shaped "ap-pSi" regions on a field of ox-pSi. When comparing the areas outside and inside the glycerol-masked pSi spots, one finds dramatic differences in the Si–O–Si, SiH x ( x = 1–3) and O y SiH x ( y, x = 1–3) levels with a spatially dependent continuum of compositions across the spot diameter. Experimental conditions could be adjusted to tune the final ap-pSi spot diameter and edge widths from 90 µm to 520 µm and 20 µm to 130 µm, respectively. The resulting ap-pSi spot diameter is explained by using molecular kinetic theory and time-dependent glycerol imbibement into the pSi within a one-dimensional Darcy's law model.